Bio-based light-healing isocyanate-free polyurethanes derived from carbonated soybean oil and coumarin - Karteek Boga; Nikhil Rambharosh Dhore; Aruna Palanisamy; Antonio F. Patti; John C. Warner; George P. Simon; Kei Saito (Green Chemistry Letters and Reviews, 2023)
ABSTRACTIn response to environmental concerns and restrictions on isocyanate-based materials, researchers and the coatings industry are focused on developing eco-friendly isocyanate-free polyurethanes. This article introduces a novel class of environmentally-friendly, initiator/catalyst-free, UV-curable, self-healing non-isocyanate polyurethanes (NIPUs) synthesized from bio-based carbonated soybean oil (CSO) and non-toxic coumarin. The synthesis of these polymers is based on using a photo-reactive coumarin that undergoes a reversible [2 + 2] cycloaddition upon exposure to the wavelength of UV light. UV-curable three coumarin-terminated isocyanate-free polyurethane prepolymers were synthesized using CSO and three different amines and epoxy coumarin. Subsequently, a set of cross-linked NIPU polymers were obtained with exposure of 365 nm UV irradiation. The photo-reversible nature of these polymers was investigated in response to various wavelengths of UV radiation. Additionally, their self-healing ability and the thermal and mechanical properties of NIPU coatings were studied using optical microscopy, thermogravimetric analysis, differential scanning calorimetry, and a universal testing machine. The outcomes demonstrate that this polyurethane has the potential to provide a sustainable alternative to isocyanate-based materials. Two examples of stimulated healing are given, that of healing a scratch and the other being the healing of a sample that has been mechanically stressed to failure in a tensile mode.